Study of Nepheroblastoma Overexpressed Protein (NOV/CCN3) as a Biomarker in Serum of Iraqi Patients with Rheumatoid Arthritis - Mihad M. Hamid, Bushra F. Hassan, Ali Hussein Al-Hafidh, Samer Abdulhassn Muhi, Mohammed A. Al-Hashemi (Pakistan Journal of Medical & Health Sciences, 2022)
Rheumatoid arthritis (RA) is a systemic autoimmune condition that is chronic, inflammatory, and can affect any joint in the body. Rheumatoid arthritis is defined by symmetric inflammation of synovial joints, which can eventually lead to the erosion of cartilage and bone. The objective of this study was to measure CCN3, CRP, I.R, Insulin .F.G, and Lipid profiles in patients with Rheumatoid arthritis. The current study comprised a total of 120 participants, who were separated into two groups. Group1 contained 70 Rheumatoid arthritis patients, and group2 controls 50; the samples were extracted from women and man, the levels of CCN3, CRP, I.R .F.G, Insulin, Cholesterol, TG, VLDL, LDL, and HDL were evaluated. The levels of PTX3 and Insulin were determined using an enzyme-linked immunosorbent assay (ELISA), and the stories of F.G, Cholesterol, TG, CRP, VLDL, LDL, and HDL, were assayed using a spectrophotometer. The result of CCN3 shows a high significant change among two groups' patients RA and control. Systole, Diastole, and LDL values have non-significant change in their levels in RA patients. Triglyceride, Cholesterol, HDL, VLDL, CRP, Insulin, F.G, and I.R values have a significant change in their levels in patients RA. Conclusion: According to the presented results CCN3, CRP, I.R .F.G, Insulin, T.G, Cholesterol, VLDL, and HDL all have an effect on RA patients. RA patients are not affected by their systole, diastole, or LDL levels.